New fossil Praeaulacinae wasps (Insect: Hymenoptera: Evanioidea: Praeaulacidae) from the Middle Jurassic of China - Li, Longfeng; Shih, Chungkun; Ren, Dong (Zootaxa, 2014)
A new genus with a new species, Archaulacus probus gen. et sp. nov., and two new species, Praeaulacus subrhombeus sp. nov., P. tenellus sp. nov., belonging to the subfamily Praeaulacinae (Praeaulacidae) are described and illustrated. The specimens were collected from the Middle Jurassic of Jiulongshan Formation at Daohugou in Inner Mongolia, China. Archaulacus gen. nov. differs from other genera of Praeaulacinae in having the first abscissa of Rs of the fore wing subvertical to R and 2m-cu slightly basad of 2r-m. This is the first time that these characters are reported for the Praeaulacinae. Based on new information provided by the new species, an updated key to the known species of Praeaulacus is provided.